(untitled) (Bangladesh Journal of Zoology, 2016)
Habitat selection of common skipper frog [Euphlyctis cyanophlyctis (Schneider, 1799)] was studied by a sampling (covering all the three seasons) of data collection on six abiotic (size and depth of water body, air and water temperature, dissolved oxygen and free carbon dioxide) and three biotic (plant species richness, zooplankton species richness and zooplankton density) factors of three ponds in Chittagong, Bangladesh. The discriminant analysis, cluster analysis and paired t-test of total data revealed that the three water bodies functioned as separate systems. Of the nine factors, only four (AT, WT, FCO2 and Zp_den) had individual significant influence on the frog at least at one of the ponds. However, the maximum R2 value (0.712, p < 0.001) indicates that at least some important factors were not included in the investigation. Bangladesh J. Zool. 44(1): 133-146, 2016